2024
DOI: 10.1021/acsbiomaterials.3c01810
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Loading and Sustained Delivery of Methotrexate Using a Tip-Swellable Microneedle Array Patch for Psoriasis Treatment

Puxuan Zhao,
Zhiming Li,
Zhixin Ling
et al.

Abstract: Methotrexate (MTX), a primary treatment for moderate to severe psoriasis, is limited in clinical use due to suboptimal results and severe side effects from subcutaneous (SC) injection and oral administration. Microneedles offer a promising alternative for direct MTX delivery to targeted skin lesions, but issues such as drug wastage, dosage inaccuracy, and limited drug residence time in the lesions remain. This study introduces a tipswellable microneedle array patch (TSMAP) using photo-crosslinked methacrylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…By offering a user-friendly and efficient alternative for administering methotrexate, this design reduces side effects and improves drug retention at the target site. Such advancements could significantly decrease the overall treatment burden for patients [ 47 ].…”
Section: Potential Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…By offering a user-friendly and efficient alternative for administering methotrexate, this design reduces side effects and improves drug retention at the target site. Such advancements could significantly decrease the overall treatment burden for patients [ 47 ].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…One study demonstrated the fabrication of light-responsive hydrogel-forming microneedle arrays using micromolding capable of delivering ibuprofen upon exposure to light, thus enabling controlled, on-demand drug release [ 9 ]. Another study introduced a tip-swellable microneedle array patch (TSMAP) for the sustained delivery of methotrexate (MTX) in psoriasis treatment using photo-crosslinked methacrylated hyaluronic acid (MeHA) and biocompatible resin, ensuring efficient drug loading and minimal wastage [ 47 ]. Research has also explored hydrogel swelling to trigger the release of biodegradable polymer microneedles, showing sustained drug release and effective delivery of model drugs by micromolding poly-lactic-co-glycolic acid (PLGA) after filling the cavities of the mold with hydrogel microparticles [ 82 ].…”
Section: Processes Involved In the Manufacturing Of Swellable Microne...mentioning
confidence: 99%
See 3 more Smart Citations